Adaptable surfactant-mediated method for the preparation of anisotropic metal chalcogenide nanomaterials - McCarthy, S. A. (Sci Rep, 2018)
The hot injection synthesis of nanomaterials is a highly diverse and fundamental field of chemical research, which has shown much success in the bottom up approach to nanomaterial design. Here we report a synthetic strategy for the production of anisotropic metal chalcogenide nanomaterials of different compositions and shapes, using an optimised hot injection approach. Its unique advantage compared to other hot injection routes is that it employs one chemical to act as many agents: high boiling point, viscous solvent, reducing agent, and surface coordinating ligand. It has been employed to produce a range of nanomaterials, such as CuS, Bi(2)S(3), Cu(2-x)Se, FeSe(2), and Bi(4)Se(3), among others, with various structures including nanoplates and nanosheets. Overall, this article will highlight the excellent versatility of the method, which can be tuned to produce many different materials and shapes. In addition, due to the nature of the synthesis, 2D nanomaterial products are produced as monolayers without the need for exfoliation; a significant achievement towards future development of these materials.